Apocynaceae Plants: Ethnobotany, Phytochemistry, Bioactivity and Biotechnological Advances – Book Review - Ahmad Reza Maulana (Ethnobotany Research and Applications, 2025)
Biotechnological Advances. Springer, Singapore. pp 263. EUR €117.69 (eBook), ISBN 978-981-99-5406-3 (eBook). As revealed in Apocynaceae Plants: Ethnobotany, Phytochemistry, Bioactivity and Biotechnological Advances, edited by Ravindra H. Patil, Mohini P. Patil, and Vijay L. Maheshwari (2023), the book presents the latest research on the Apocynaceae plant family, with a specific focus on ethnobotanical uses, phytochemistry, and bioactive compounds. The application of the plants is significant, given that they have been used widely for medicinal purposes and have potential use as drugs. With the increasing demand for novel bioactive molecules, this book is a valuable resource for researchers in medicinal chemistry, pharmacology, and biotechnology.